Effects of disordered microstructure and heat release on propagation of combustion front. Issue 1 (31st December 2016) - Naine, Tarun Bharath; Gundawar, Manoj Kumar
Abstract: Numerical experiments for diagnosis of combustion of actual heterogeneous systems are performed on a one-dimensional chain. The internal microstructure of actual heterogeneous systems is apriori unknown, various distributions like uniform, beta, and normal have been considered for distributing neighboring reaction cells. Two cases, for the nature of distribution of heat release of reaction cells are taken into account, one with identical heat release and the other with disordered heat release. Role of different random distributions in describing heterogeneous combustion process is established in present paper. Particularly, the normal distribution of arranging neighboring reaction cells has been found to be powerful methodology in explaining the combustion process of an actual heterogeneous system at higher ignition temperatures for both cases of distributing heat release. Validation of the developed model with the experimental data of combustion of the CMDB propellants, gasless Ti + x Si system, and different thermite mixtures is performed. Our results show that the experimental burning rates at higher ignition temperatures (ε > 0.32) of the heterogeneous system are better reproduced theoretically with the present model. We have also shown that different combustion limits for different thermite systems are the consequences of disordered heat release. Experimental data for thermite systems that have lower inflammability limits are analyzed in the view of disordered heat releases of cells. The model developed in the view of disordered heat releases reproduces the experimental burn rates and experimental combustion limit.